Blockchain Technology and Its Untapped Potentials in the Hospitality Industry - Karim, Rashed; Ishrat, Mahima; Rahman, Mohammad Ashequr (Journal of Technology Management and Business, 2022)
Blockchain technology has recently emerged as a contentious issue in academics and industry. Financial institutions have responded immediately to the adoption of blockchain technology. The remarkable features of this technology, such as high security, dependability, and efficiency, have made it extremely popular in the financial sector. However, the hospitality and tourism industries are blissfully unaware of this new blockchain technology and its exceptional services. Furthermore, the notion of blockchain is still foggy and poorly understood, and information on the level of knowledge and application of blockchain in the hospitality industry is very few. This research thus aims to highlight the blockchain's standard features, advantages, and applications in the hospitality industry. This study has been carried out based on secondary data sources. Specifically, journal articles, book chapters, organisational publications, website materials, and other sources have been used for data and information generation. To better operational efficiency and revenue generation and improve privacy and security, the study examines the consequences and several advantages of blockchain technology using secondary sources. The study contributes to a comprehensive understanding of blockchain technology and the benefits and diverse uses of blockchain technology in the hospitality industry.